2021
DOI: 10.31436/jop.v1i2.67
|View full text |Cite
|
Sign up to set email alerts
|

review of black seed extract as an agent in the wound healing process

Abstract: Introduction: Nigella Sativa or Black Cumin is an annual flowering plant that can be used for wound treatment. In the treatment for wound healing, this plant contains many beneficial components that can help with the treatment but this plant utilisation in the medical field is still limited. This review will provide an overview of the advantages when this plant is used in the wound healing treatment. Method: The review was based on the ROSES protocol, and the databases used were ScienceDirect, PubMed, and Goog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Black seed oil, on the other hand, contains 30% to 40% oil and is particularly rich in thymoquinone, a type of antioxidant [ 31 , 32 ], along with phenols, linoleic acid, and oleic acid, which various studies have shown to be effective in wound healing [ 33 ]. Studies have shown that black seed oil is suitable for wound healing in the human body and can prevent infection [ 35 , 39 ]. Moreover, combining black seed oil with olive oil enhances its antioxidant properties [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Black seed oil, on the other hand, contains 30% to 40% oil and is particularly rich in thymoquinone, a type of antioxidant [ 31 , 32 ], along with phenols, linoleic acid, and oleic acid, which various studies have shown to be effective in wound healing [ 33 ]. Studies have shown that black seed oil is suitable for wound healing in the human body and can prevent infection [ 35 , 39 ]. Moreover, combining black seed oil with olive oil enhances its antioxidant properties [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, most of the plant’s properties are attributed to thymoquinone [ 38 ]. Studies have shown that black seed is suitable for promoting wound healing in the human body and can help prevent infections [ 35 , 39 ]. Furthermore, adding black seed oil to olive oil enhances its antioxidant properties [ 40 ].…”
Section: Introductionmentioning
confidence: 99%